Effect of carbon content on the microstructure and mechanical properties of high-entropy (Ti0.2Zr0.2Nb0.2Ta0.2Mo0.2)Cx ceramics. Issue 2 (February 2022) - Luo, Si-Chun; Guo, Wei-Ming; Fang, Ze-Lin; Plucknett, Kevin; Lin, Hua-Tay
Abstract: High-entropy (Ti0.2 Zr0.2 Nb0.2 Ta0.2 Mo0.2 )Cx ceramics, with different carbon contents (x=0.55−1), were prepared by spark plasma sintering using powders synthesized via a carbothermal reduction approach. Single-phase, high-entropy (Ti0.2 Zr0.2 Nb0.2 Ta0.2 Mo0.2 )Cx ceramics could be obtained when using a carbon content of x=0.70−0.85. Combined ZrO2 and Mo-rich carbide phases, or residual graphite, existed in the ceramics due to either a carbon deficiency or excess at x=0.55 and 1, respectively. With the carbon content increased from x=0.70 to x=0.85, the grain size decreased from 4.36 ± 1.55 μm to 2.00 ± 0.91 μm, while the hardness and toughness increased from 23.72 ± 0.26 GPa and 1.69 ± 0.21 MPa·m 1/2 to 25.45 ± 0.59 GPa and 2.37 ± 0.17 MPa·m 1/2, respectively. This study showed that the microstructure and mechanical properties of high-entropy carbide ceramics could be adjusted by the carbon content. High carbon content is conducive to improving hardness and toughness, as well as reducing grain size.